BATAS AKHIR WAKTU SHOLAT MENURUT 4 IMAM MAZHAB - Neli Maryam Sanjung; Jamhuri, Jamhuri; Amri, Aulil (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2024)
Sholat is an essential pillar of Islam, performed five times a day as a means of communication between the servant and God, as well as a reminder of religious duties and moral values.This study discusses the differences of opinion regarding the time limits for prayer according to the four Imam Mazhabs. The aim of this research is to understand the differing views on prayer times, which are derived from the fiqh literature of the Imam Mazhabs. Using a qualitative research approach with a descriptive-analytic method, the study gathers data through literature review. The findings of the research indicate that the time limits for prayer according to the four Mazhabs vary. According to the Hanafi Mazhab, the time for prayer starts with clear natural phenomena, such as the decline of the sun for Zuhr, and extends until the middle of the night for Isha. The Maliki Mazhab also refers to the movement of the sun but places more emphasis on the consensus of the companions and the followers (tabi'in) in determining the time. Meanwhile, the Shafi'i Mazhab is stricter in determining the time limits for prayer, while the Hanbali Mazhab prioritizes ease for Muslims to perform their worship according to their circumstances, without overly burdening them with rigid regulations.